Militant Jihadism : Today and Tomorrow - Pektas, Serafettin; Leman, Johan; Pektas, Serafettin; Leman, Johan (Leuven Leuven University Press, 2019)
"Jihadist militants keep being a global threat. Many observers suggest that a transformation is likely to happen in their organisation, operation, mobilisation, and recruitment strategies, particularly after the territorial decline of the Caliphate of the Islamic State. This volume explores different aspects of the future trajectories of militant jihadism and the prospective transformation of this movement in and around Europe. The authors analyse the changing jihadist landscape and networks, and the societal challenges posed by both returned foreign terrorist fighters and those who have not returned to their countries of origin. Other topics of discussion are cyber jihadism, jihadist financing, women's position in and relevance for contemporary jihadism, the role of prisons in relation to radicalisation and militancy, and the changing theological dynamics. Based on recent empirical research, Militant Jihadism offers a solid scholarly contribution to various disciplines that study violence, terrorism, security, and extremism. Contributors: Mohamed-Ali Adraoui (Georgetown University), Laith Alkhouri (Flashpoint), Nadim Houry (Arab Reform Initiative), Adolfo Gatti (Lumina Analytics), Stef Janssens (MYRIA), Johan Leman (KU Leuven), Serafettin Pektas (Researcher), Anita Perešin (Office of the National Security Council of the Republic of Croatia), Teun van Dongen (Independent Security Expert), Arturo Varvelli (ISPI)."
English
Keywords: Religious fundamentalism; Islam; Sociology; Terrorism, armed struggle; Terrorist attack; Jihadism; Extremism; Islamic State; Cyberjihadism; Foreign Fighters; Urban Terrorist Sanctuary; Salafism; Libya; Jihadist Women; Muslim Critiques of Jihadism; Jihadist Financing